Biomaterials and Electroactive Bacteria for Biodegradable Electronics - Bonné, Robin; Wouters, Koen; Lustermans, Jamie J. M.; Manca, Jean V. (Frontiers in Microbiology, 2022)
The global production of unrecycled electronic waste is extensively growing each year, urging the search for alternatives in biodegradable electronic materials. Electroactive bacteria and their nanowires have emerged as a new route towards electronic biological materials (e-biologics). Recent studies on electron transport in cable bacteria – filamentous, multicellular electroactive bacteria - showed centimeter long electron transport in an organized conductive fiber structure with high conductivities and remarkable intrinsic electrical properties. In this work we give a brief overview of the recent advances in biodegradable electronics with a focus on the use of biomaterials and electroactive bacteria, and with special attention for cable bacteria. We investigate the potential of cable bacteria in this field, as we compare the intrinsic electrical properties of cable bacteria to organic and inorganic electronic materials. Based on their intrinsic electrical properties, we show cable bacteria filaments to have great potential as for instance interconnects and transistor channels in a new generation of bioelectronics. Together with other biomaterials and electroactive bacteria they open electrifying routes towards a new generation of biodegradable electronics.